DISTRIBUCION DE LA FAMILIA TROGIDAE EN MEXICO (COLEOPTERA LAMELLICORNIA) - Deloya, Cuauhtémoc (Instituto de Ecología, A.C., 2000)
Based in the revision of nearly 800 specimens, an actualized distribution list of Mexican Trogidae is presented. In Mexico, there are 9 species of Trox Fabricius and 18 species of Omorgus Erichson, being T. scaber (Linnaeus), O. howelli Howden & Vaurie, O. monachus Herbst and O. scabrosus Beauvois new Mexican records. The Mexican states with more specific richness of Trox are: Durango with 6, followed by Chihuahua, Nuevo León and Veracruz, each with four species. The Mexican States with more specific richness of Omorgus are: Sonora with 8, Chihuahua, Nuevo León and Tamaulipas with 6, and Coahuila, Morelos, Puebla and Veracruz, each with 5 species. Species that show the broadest distribution at state level are: O. suberosus Fabricius (20), T. plicatus LeConte (13), O. rubricans Robinson (11), T. spinulosus dentibus Robinson and O. fuliginosus Robinson (9), O. punctatus Germar and O. scutellaris Say (8) and T. variolatus Melsheimer, T. sonorae LeConte and T. aequalis Say (6). Finally, from the 27 species of Mexican Trogidae, O. tomentosus Harold, O. mictlensis Deloya and T. acanthinus Harold can be considered as endemic species.